Host Epithelial Interactions with Helicobacter Pylori: A Role for Disrupted Gastric Barrier Function in the Clinical Outcome of Infection? - Andre G Buret; Jason P Fedwick; Andrew N Flynn (Canadian Journal of Gastroenterology)
Infection of the human stomach with Helicobacter pylori may develop into gastritis, ulceration, adenocarcinoma and mucosal lymphomas. The pathogenic mechanisms that determine the clinical outcome from this microbial-epithelial interaction remain poorly understood. An increasing number of reports suggests that disruptions of epithelial barrier function may contribute to pathology and postinfectious complications in a variety of gastrointestinal infections. The aim of this review is to critically discuss the implications of H pylori persistence on gastric disease, with emphasis on the role of myosin light chain kinase, claudins and matrix metalloproteinases in gastric permeability defects, and their contribution to the development of cancer. These mechanisms and the associated signalling events may represent novel therapeutic targets to control disease processes induced by H pylori, a microbial pathogen that colonizes the stomach of over 50% of the human population.